The Important Role of Extensive Reading Strategy in Indonesian EFL Learning Contexts - Wijaya, Kristian (LPPM Universitas Advent Indonesia, 2021)
Abstract Academic literacy is one of the paramount global competencies that should be mastered by worldwide university academicians including Indonesian EFL learners. To fully fulfill this holistic educational objectivity, extensive reading plays a key role in fostering overarching Indonesian EFL learners’ target language proficiency due to the inducement of pleasurable, continual, and stress-free L2 reading learning dynamics proffered by this student-centered learning approach. Furthermore, the researcher attempted to delve more profoundly regarding the important role of extensive reading strategy in Indonesian EFL learning contexts. This present qualitative study harnessed a document analysis approach to yield renewable insights for Indonesian EFL experts, practitioners, researchers, and educators concerning the influential impacts potentially promoted by extensive reading strategy implementations. The research results indicated that the inducement of contextual and continual extensive reading activities had successfully improved EFL learners’ L2 reading interest and competencies. Future researchers are advocated to conduct a more exhaustive document analysis on the contrary beliefs and perilous effects generated by extensive reading approach to better impart more appropriate extensive reading programs applicable for Indonesian EFL learners’ reading needs, interests, and levels. Keywords: document analysis, extensive reading strategy, Indonesian EFL learning contexts